Recent advances in ultrasonic assisted turning: A step towards sustainability. Issue 1 (31st December 2016) - Sharma, Varun; Pandey, Pulak M.
Abstract: In order to meet the stringent environmental obligations, the research in the recent past has been focused on adopting sustainable techniques in industrial sector. Ultrasonic assisted turning (UAT) process has been developed in this regard to machine difficult to cut materials like alloys of nickel, titanium and composite materials. The present paper presents a thorough literature review to highlight the advantages in terms of low cutting forces and stress levels developed in UAT as compared to conventional turning process. In UAT, the cutting tool is imparted ultrasonic vibrations and hence an intermittent cutting mechanism is dominant. A decreased tool wear accompanied with compressive residual stresses in the machined part has made UAT a viable alternative to machine the advanced materials. The chip analysis has been shown to indicate that there occurs less plastic deformation in the material during UAT. The main objective of the present review article is to highlight advantages of UAT and to encourage the same by discussing a way forward to make it cost effective and environment friendly by reducing the carbon footprints of machining.